Three year results of Blessed: Expanded access for DeltaRex-G for an intermediate size population with advanced pancreatic cancer and sarcoma (NCT04091295) and individual patient use of DeltaRex-G for solid malignancies (IND# 19130) - Chawla, Sant P.; Wong, Steven; Quon, Doris; Moradkhani, Ania; Chua, Victoria S.; Brigham, Don A.; Reed, Rebecca A; Swaney, William; Hall, Frederick L.; Gordon, Erlinda M. (Frontiers in Molecular Medicine, 2022)
Background: Innovative treatments are urgently needed for metastatic cancer. DeltaRex-G, a tumor-targeted retrovector encoding a dominant-negative / cytocidal cyclin G1 (CCNG1 gene) inhibitor construct—has been tested in over 280 cancer patients worldwide in phase 1, phase 2 studies and compassionate use studies, demonstrating long term (>10 years) survivorship in patients with advanced cancers, including pancreatic cancer, osteosarcoma, malignant peripheral nerve sheath tumor, breast cancer, and B-cell lymphoma. Patient and Methods: Endpoints: Survival, response, treatment-related adverse events. Study 1 is entitled “Blessed: Expanded Access for DeltaRex-G for Advanced Pancreatic Cancer and Sarcoma (NCT04091295)”. Study 2 is entitled “Individual Patient Use of DeltaRex-G for Solid Malignancies (IND#19130). In both studies, patients will receive DeltaRex-G at 1-3 x 10e11 cfu i.v. over 30-45 minutes, 3 x a week until significant disease progression or unacceptable toxicity or death occurs. Results: Seventeen patients were enrolled, 9 sarcoma, 2 pancreatic adenocarcinoma, 1 non-small cell lung cancer, 2 breast carcinoma, 1 prostate cancer, 1 cholangiocarcinoma and 1 basal cell carcinoma and actinic keratosis. Three patients were enrolled in Study 1 and 14 patients were enrolled in Study 2. Twelve of 17 enrolled patients were treated with DeltaRex-G monotherapy or in combination with United States Food and Drug Administration-approved cancer therapies. Five patients died before receiving DeltaRex-G. Efficacy Analysis: Of the 12 treated patients, 5 (42%) are alive 15 to 36 months from DeltaRex-G treatment initiation. Two patients with early-stage HR+ HER2+ positive or triple receptor negative invasive breast cancer who received DeltaRex-G as adjuvant/first line therapy are alive in complete remission 23 and 16 months after DeltaRex-G treatment initiation respectively; 3 patients with metastatic chordoma, chondrosarcoma and advanced basal cell carcinoma are alive 36, 31 and 15 months after DeltaRex-G treatment initiation respectively. Safety Analysis: There were no treatment-related adverse events reported. Conclusions: Taken together, the data suggest that (1) DeltaRex-G may evoke tumor growth stabilization after failing standard chemotherapy, (2) DeltaRex-G may act synergistically with standard chemotherapy/targeted therapies, and (3) Adjuvant/first line therapy with DeltaRex-G for early-stage invasive carcinoma of breast may be authorized by the USFDA when patients refuse to receive toxic chemotherapy.